Abstract 9851: LncAPAT Promotes Lipid Phagocytosis and Monocyte Adhesion in Atherosclerosis Through miR-107/NOR1 Axis - Kamili, Adalaiti; Han, Shuang; Chen, Yu; Zhang, Weili (Circulation (New York, N.Y.), 2022)
IntroductionAtherosclerosis is a chronic inflammatory disorder characterized by excessive lipid deposition in the arterial intima. MicroRNA (miR)-107 was reported to inhibit the development of atherosclerosis, but it is unclear whether miR-107 regulate lipid phagocytosis of macrophages. HypothesisIn the present study, we hypothesized that the potential interaction of lncAPAT and miR-107 may regulates the development of atherosclerosis. Methods and resultsWe used real-time quantitative PCR (RT-qPCR) to determine the expression levels of miR-107 in peripheral blood mononuclear cells (PBMCs) from patients with coronary artery atherosclerosis and control subjects without plaque. Bioinformatics analysis, dual-luciferase reporter and RNA immunoprecipitation (RIP) assays were used to verify the interaction between lncRNA atherosclerotic plaque instability-associated transcript (lncAPAT) and miR-107. We found that miR-107 was highly expressed in the PBMCs of patients with atherosclerotic plaques, and that lncAPAT acted as a competing endogenous RNA to decrease the expression of miR-107. In addition, miR-107 inhibited monocyte adhesion and lipid phagocytosis of macrophages, while lncAPAT promoted monocyte adhesion and lipid phagocytosis via binding with miR-107. Further experiments identified neuron-derived orphan receptor 1 (NOR1) as a downstream target of miR-107 that was up-regulated by lncAPAT. In vitro and in vivo studies revealed that lncAPAT promoted monocyte adhesion and lipid phagocytosis of macrophages by functioning as a ceRNA to up-regulate NOR1 by sponging miR-107. ConclusionsOur study demonstrates that lncAPAT regulates the miR-107/NOR1 axis to promote lipid phagocytosis by macrophages, indicating that it may serve as a potential therapeutic target for atherosclerotic disease.